Prospect of research hotspots in prevention and treatment of diseases based on intestinal microbiome - Cai, Yue; Zhang, Yuting; Wang, Wenxue; Geng, Jiawei (Frontiers in Immunology, 2022)
Although the regulation of gut microbiota is gradually widely used in the prevention and treatment of various diseases, there is still a lack of effective methods. Therefor, researcher must focus on how to accurately regulate gut microbiota. In order to promote the rapid development of this field, we provide several insights in gut microbiome-based precision therapies while prospecting the future directions.